Beeswax Alcohol (BWA, Raydel®) Improved Blood Oxidative Variables and Ameliorated Severe Damage of Zebrafish Kidneys, Testes, and Ovaries Impaired by 24-Week Consumption of a High-Cholesterol and High-Galactose Diet: A Comparative Analysis with Coenzyme Q10 - Kyung-Hyun Cho; Ashutosh Bahuguna; Ji-Eun Kim; Yunki Lee; Sang Hyuk Lee; Cheolmin Jeon; Cheol-Hee Kim (Pharmaceuticals)
Objectives: The present study describes the comparative effect of 24-week supplementation of beeswax alcohol (BWA, Raydel®, 0.5% and 1.0%, wt/wt) and coenzyme Q10 (CoQ10, 0.5% and 1.0%, wt/wt) on plasma oxidative variables and the prevention of organ injury in adult zebrafish subjected to a high-cholesterol (HC, 4%, wt/wt) and -D-galactose (Gal, 30%, wt/wt) diet. Methods: Adult zebrafish were fed various HC+Gal diets enriched with either BWA or CoQ10. After 24 weeks of dietary intervention, blood and organs were harvested for subsequent biochemical and histological evaluations. Results: The HC+Gal-elevated plasma oxidative variables were reverted by the consumption of BWA, marked by the lowest plasma malondialdehyde (MDA) level and highest sulfhydryl content. The HC+Gal-impaired zebrafish swimming ability (staggering movement) was substantially recovered by BWA, manifested by a ~three-fold (p < 0.001) enhancement in swimming distance and speed. Also, the intake of BWA affected the morphology of HC+Gal-compromised kidney and induced histological changes by mitigating reactive oxygen species (ROS) production and cellular senescence, which was markedly more effective than the results seen in the CoQ10 group. Likewise, BWA proved effective in preventing HC+Gal-induced testis damage, apparent in the 48.3% (p < 0.05) higher spermatozoa and 26.3% (p < 0.01) reduced interstitial space between the seminiferous tubules. BWA substantially prevented HC+Gal-induced ovary damage by suppressing oxidative stress, lipid deposition and senescence, leading to the restoration of mature vitellogenic oocyte counts. Conclusion: BWA demonstrated a greater ability than CoQ10 to enhance plasma antioxidant status, suppress ROS generation, delay organ aging and alleviate HC+Gal-induced adversity in zebrafish.